Methodology of integrated teaching of Georgian language and literature. Motivation and its types - Jinjikhadze, Levan (COLLECTION OF SCIENTIFIC WORKS OF SOKHUMI UNIVERSITY, 2023)
The article, first of all, analyzes the importance of teaching-learning, talks about the fact that the teaching-learning process is especially active when it is directed to the student’s research interests, and that the concept of teaching-learning includes didactic research, time distribution of teaching activities, teacher and student roles interdependence, determination of anticipatedoutcomes. The focus is also on three levels of any science methodology: general methodology, specific methodology, and private methodology. Two types of teaching methods are presented, in a broad sense, the method-concept - a set of teaching ways and means, and teaching method in a narrow sense-the method involves the determined means of teacher-student interaction under the direct guidance of a teacher, directed at achieving educational, formative and didactic goals. Everyone knows that there are the following types of motivation: internal and external, but there is not a proper focus on other types of motivation, which is the objective our study. Hence, we have a positive and negative motivation, sustainable and unsustainable motivation, individual, group and cognitive ones.